Coffee grounds in swine rations - Balogun, T.F.; Koch, B.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
As little as 10% of coffee grounds depressed the feed intake and growth rate of growing pigs and finishing pigs. Apparently, reduced growth rate resulted from lack of palatability rather than any toxic factor in the coffee grounds.
Swine Industry Day 1973 is known as Swine Day, 1973
Keywords: Swine; Coffee gounds; Palatability; Growing pigs; Finishing pigs